Cultural Adaptation and Validation of the Urdu Version of the Cognitive Emotion Regulation Questionnaire (CERQ) in Male Patients With Substance Use Disorders (SUDs) in Pakistan - Shahzad, Salman; Bano, Nasreen; Begum, Nasreen; Jones, Hendrée E. (Frontiers in Psychiatry, 2022)
Background Adults with substance use disorders (SUDs) often have co-occurring mental health problems. Emotion regulation may play a vital role in mental health problems. The Cognitive Emotion Regulation Questionnaire (CERQ) is a widely used measure for assessing cognitive emotion regulation. However, it has not been used in Pakistan on patients with co-occurring SUDs and mental health issues. The present study aims to translate and adapt the CERQ into the Urdu language and to determine its reliability and convergent validity in a sample of male patients with SUDs in Pakistan. Method Participants completed a demographic information form, the CERQ, the Depression, Anxiety, and Stress Scale Short Form [DASS-21)], and the Rosenberg Self-Esteem Scale [RSES)] in Urdu. Results Male participants (N = 237) 18–50 years of age (M = 29.8, SD = 8.1) were recruited from four substance use disorder treatment centers and hospitals in Karachi. The reliability of the Urdu version of the CERQ was based on an examination of its internal consistency reliability (Cronbach's α) and test–retest reliability for both the total scale and its subscales. Internal consistency for the CERQ total (α = 0.80) was adequate, as it was for subscales of self-blame, (0.76) acceptance (0.78), rumination (0.72), positive refocusing (0.79), focus on planning (0.89), positive reappraisal (0.81), putting into perspective (0.83), catastrophizing (0.73), and other blame (0.70). The 10–14 day test–retest reliability of the CERQ total score was 0.86. Higher CERQ scores were significantly (ps < 0.001) negatively associated with DASS-21depression (r = –0.24), anxiety (r = –0.23), and stress (r = –0.27) subscales, as well as the DASS-21 total score (r = –0.26) and positively associated with the RSES self-esteem score (r = 0.30). Conclusion The Urdu version of the CERQ is a reliable measure for investigating cognitive emotion regulation strategies related to mental health and SUDs in Pakistan.